Cardiac donation after circulatory determination of death: protocol for a mixed-methods study of healthcare provider and public perceptions in Canada. Issue 7 (20th July 2020) - Honarmand, Kimia; Ball, Ian; Weiss, Matthew; Slessarev, Marat; Sibbald, Robert; Sarti, Aimee; Meade, Maureen; D'Aragon, Frédérick; Chasse, Michael; Basmaji, John; Parsons Leigh, Jeanna
Abstract : Introduction: Cardiac transplantation remains the best treatment for patients with end-stage heart disease that is refractory to medical or device therapies, however, a major challenge for heart transplantation is the persistent discrepancy between the number of patients on waiting lists and the number of available hearts. While other countries (eg, UK, Australia and Belgium) have explored and implemented alternative models of transplantation, such as cardiac donation after circulatory determination of death (DCDD) to alleviate transplantation wait times, ethical concerns have hindered implementation in some countries. This study aims to explore the attitudes and opinions of healthcare providers and the public about cardiac DCDD in order to identify and describe opportunities and challenges in ensuring that proposed cardiac DCDD procedures in Canada are consistent with Canadian values and ethical norms. Methods and analysis: This study will include two parts that will be conducted concurrently. Part 1 is a qualitative study consisting of semi-structured interviews with Canadian healthcare providers who routinely care for organ donors and/or transplant recipients to describe their perceptions about cardiac DCDD. Part 2 is a convergent parallel mixed-methods design consisting of a series of focus groups and follow-up surveys with members of the Canadian general public to describe their perceptions about cardiac DCDD. Ethics and dissemination: This study has been approved by the Research Ethics Board at Western University. The findings will be presented at regional and national conferences and reported in peer-reviewed publications.